2016
DOI: 10.1038/srep28785
|View full text |Cite
|
Sign up to set email alerts
|

Projected asymmetric response of Adélie penguins to Antarctic climate change

Abstract: The contribution of climate change to shifts in a species’ geographic distribution is a critical and often unresolved ecological question. Climate change in Antarctica is asymmetric, with cooling in parts of the continent and warming along the West Antarctic Peninsula (WAP). The Adélie penguin (Pygoscelis adeliae) is a circumpolar meso-predator exposed to the full range of Antarctic climate and is undergoing dramatic population shifts coincident with climate change. We used true presence-absence data on Adélie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 37 publications
5
62
0
1
Order By: Relevance
“…Modelling studies that forecast population trends for pelagic penguins under future climate change scenarios should incorporate the dispersal patterns that we have outlined here, as in a recent study of emperor penguins (Jenouvrier et al., ). The conclusions of modelling studies for pelagic penguins that do not incorporate dispersal (Abadi, Barbraud, & Gimenez, ; Cimino et al., ; Jenouvrier et al., ) should be treated with caution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modelling studies that forecast population trends for pelagic penguins under future climate change scenarios should incorporate the dispersal patterns that we have outlined here, as in a recent study of emperor penguins (Jenouvrier et al., ). The conclusions of modelling studies for pelagic penguins that do not incorporate dispersal (Abadi, Barbraud, & Gimenez, ; Cimino et al., ; Jenouvrier et al., ) should be treated with caution.…”
Section: Discussionmentioning
confidence: 99%
“…This appears to be the case for Antarctic and sub‐Antarctic penguins, but they present a significant logistical challenge for studying dispersal (defined here as movement away from natal colonies to alternate breeding sites), as the vast majority of colonies are in remote locations. Banding studies initially suggested a high degree of philopatry in many species (Weimerskirch, Jouventin, Mougin, Stahl, & Van, ), and, until recently (Jenouvrier, Garnier, Patout, & Desvillettes, ), forecasts of extinction risk had not considered the potential buffering effect of dispersal (Cimino, Lynch, Saba, & Oliver, ; Jenouvrier et al., ). Genetic analyses (Clucas, Younger et al., ; Freer et al., ; Roeder et al., ; Younger, Clucas, et al., , ), observations of colony movements (LaRue, Kooyman, Lynch, & Fretwell, ) and fluctuations in colony size (Kooyman & Ponganis, ) indicate that dispersal may be common.…”
Section: Introductionmentioning
confidence: 99%
“…Sea ice has further effects on adult penguin population survival of ice‐obligatory species: Adult survival of Emperor penguins and proportion of breeders of Snow Petrels depend on the presence of ice (Jenouvrier et al, ). Any long‐term trend in decreasing sea‐ice extent could therefore force penguin migration southward (Cimino et al, ; Fretwell et al, ; see section ). Paleoecological data suggest that penguins are more likely to migrate than to adapt to new environmental conditions brought by climate change (Forcada & Trathan, ).…”
Section: Biology Ii: Food Web Of the Wgmentioning
confidence: 99%
“…An SST rise of 1-6°C by 2100 has been predicted by climate change scenarios (Rosenzweig et al 2008) and its impact could expand e.g. potential foraging habitat, although other factors such as changing wind regimes or changing conditions at breeding sites also need to be incorporated (Hazen et al 2013, Cimino et al 2016. The recent addition of future layers to the Bio-ORACLE data set (Jueterbock et al 2013) now makes data for the end of the 21st and the 22nd centuries more accessible to researchers (Krüger et al 2017).…”
Section: Sdms Of Seabird Distributions At Seamentioning
confidence: 99%
“…The breeding success and consequently the distribution of breeding colonies depends on a range of parameters including those more important at the nest, e.g. air temperature and rain, and those determining food availability in the surrounding marine environment (Cimino et al 2016). For example, an analysis of seabirds breeding on British coasts based on air and sea surface temperatures and precipitation calculated that 65% of seabird species are likely to lose breeding sites (25-100%) by 2100, and more northerly species are especially vulnerable (Russell et al 2015).…”
Section: Seabirds On Land -Colony and Nesting Sitesmentioning
confidence: 99%